Local deformation at micro‐notches and crack initiation in an intermetallic γ‐TiAl‐alloy. Issue 2 (7th October 2015) - Bode, B.; Wessel, W.; Brueckner‐Foit, A.; Mildner, J.; Wollenhaupt, M.; Baumert, T.
Abstract: The relation is studied between crack initiation from micro‐notches in a fully lamellar intermetallic γ‐TiAl alloy and the local strain field. These micro‐notches were introduced using femtosecond‐laser ablation and had dimensions below the average colony size. The specimen under investigation was then subjected to fatigue loading. Continuous monitoring using a travelling optical microscope allowed detecting microcracks at an early stage. Prior to fatigue loading, a sustained load was applied and the local strain field was determined using digital image correlation. This was supplemented by a Finite Element analysis of the notches and their neighbourhood. It was found that a crack was initiated from a notch causing high normal strains in lamella direction, whereas no crack was initiated from notches with high shear strains.